PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR UNIT PELAKSANA TEKNIS DINAS PENDAPATAN DAERAH KECAMATAN SAMARINDA UTARA - Futum Hubaib (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2018)
The purpose of this study is to know and assess the level of work performance of employees at the Regional Revenue Service Unit Technical Unit (UPT) Revenue Service District of North Samarinda.To analyze the data obtained by the author using multiple regression analysis tools and SPSS (Statistic Product and Service Solution) application Rel 22 For Windows to obtain the following results : The resulting regression equation is: Y = 1,329 + 0,282 X1 + 0,278 X2. Constant value of 1.329 states that if there are no independent variables (compensation and motivation) then the value of work achievement of 1.329.Result of F test calculation, F value count is 12,086 with 0,000 significance level because significance value less than 0,05 then existing regression can be used to predict the magnitude of work performance or it can be said that the independent variable (compensation and motivation) to the dependent variable (work performance).The value of F table with df1 = k = number of independent variables = 2 and df2 = n - k - 1 = 59 - 2 - 1 = 56, obtained F table value of 2.78. This means that F arithmetic> F table or 12.086> 2.78 so that it can be said that the compensation and motivation variables are together able to show the influence on the work performance or regression model can be used to predict the work performance, so that the first hypothesis is accepted truth.The value of R shows the number of 0.549. this means independent variables together have a relationship to work performance variable (dependent) of 0.549 or 54.9%. This relationship belongs to a moderate category of interpretation and this means that 54.9% of work performance can be explained or influenced by motivation compensation variables. While the rest of 45.1% work performance is explained or influenced by other causes beyond the variable compensation and motivation.Result of calculation of t test between variable of compensation (X1) with work performance (Y), obtained value of t compensation (X1) equal to 2,893 while t table value with df = n - k = 59 - 3 = 56, and significance level equal to 0,005 and test conducted two sides obtained t table amounted to 2.021. This indicates that t arithmetic> t table or 2.893> 2.021 which means the compensation variable (X1) is partially able to show significant influence on employee performance. While other variable that is motivation (X2) less able to predict or explain its effect to work productivity. Thus the second hypothesis submitted authors accepted the truth